2017
DOI: 10.1016/j.jjcc.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications in patients with symptomatic aortic stenosis and preserved ejection fraction: Japanese multicenter aortic stenosis, retrospective (JUST-R) registry

Abstract: This retrospective study demonstrated the current associations between the types of AS symptoms and prognosis in Japanese patients with severe AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, we conducted a scenario analysis and sensitivity analysis to adjust for such differences. In a Japanese retrospective study, the mortality of inoperable patients with heart failure was as high as PARTNER cohort B [21]. A second limitation is that we made a number of assumptions in our data set, including procedural complications, follow-up costs, and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…However, we conducted a scenario analysis and sensitivity analysis to adjust for such differences. In a Japanese retrospective study, the mortality of inoperable patients with heart failure was as high as PARTNER cohort B [21]. A second limitation is that we made a number of assumptions in our data set, including procedural complications, follow-up costs, and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese registry reported that untreated AS was associated with a mortality rate of 6.7% at 16 -month follow -up. 23 AS patients in the SILCARD registry probably had different clinical characteristics at baseline compared with other registries, which might have impacted their general prognosis. The registry mostly involved patients with symptomatic AS, excluding those with poor clinical symptoms but an increased risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies reported on V max , 8,9,17-25 six on MPG, 6,[26][27][28][29][30] seven on EOA, [31][32][33][34][35][36][37] and thirteen on multiple primary parameters. 5,7,[38][39][40][41][42][43][44][45][46][47][48] When all studies were pooled, any mention of error in measurement was made in less than half of the included studies (46%), with random measurement error (41%) more prevalent than systematic error (19%, Table 2).…”
Section: Systematic Reviewmentioning
confidence: 99%